1985
DOI: 10.2307/1938014
|View full text |Cite
|
Sign up to set email alerts
|

Mate and Nutrient Limitation of Egg‐laying in a Polyandrous Shorebird

Abstract: Spotted Sandpipers are unusual among animals in that a female's annual reproductive effort is regulated primarily by her ability to obtain mates. Males provide most of the parental care in this species. We recorded data on the abundance of food, and on the timing, number, and size of eggs laid by marked females over a 9—yr period on an island in central Minnesota, USA. The onset of egg—laying varied from year to year in association with the abundance of flying insects early in the season. After laying began, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…Multiple mates buffer the effects of nest loss on variance in female LRS. Given time constraints of a single breeding season, female spotted sandpipers theoretically are capable of producing a maximum of 4-6 clutches (Lank et al 1985). During this study, just one female produced five clutches in a season, and none produced six.…”
Section: Patterns Of Variance Between the Sexesmentioning
confidence: 82%
“…Multiple mates buffer the effects of nest loss on variance in female LRS. Given time constraints of a single breeding season, female spotted sandpipers theoretically are capable of producing a maximum of 4-6 clutches (Lank et al 1985). During this study, just one female produced five clutches in a season, and none produced six.…”
Section: Patterns Of Variance Between the Sexesmentioning
confidence: 82%
“…In the results presented here there was little to suggest that female P. lobatus were under energetic stress as a result of laying a clutch. Implicit in the energetic constraint argument is the assumption that energy reserves are depleted as a result of laying a clutch: in a review of the available evidence Erckmann (1983) concluded that female waders do not appear to use reserves in the production of eggs (see also Lank et al 1985;Reynolds 1987). The conclusion of this and other studies of phalaropes (Erckmann 1983;Reynolds 1987;Colwell and Oring, unpublished), that female phalaropes are not limited energetically, begs the question of why, after laying a clutch for a male, do female phalaropes not lay a second clutch and care for it themselves, as do some other species of waders (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In 1986 and 1987 hormonal studies that might have affected MS or RS were conducted; therefore, these years were omitted from this analysis. A detailed description of the study area and an account of the population biology of spotted sandpipers can be found elsewhere (Maxson and Oring 1980;Lank 1982, 1986;Oring et al 1983;Lank et al 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Several factors contributed to this pattern. Whereas female MS ranged from 1 to 4 or 5 annually (Lank et al 1985), parental investment patterns limit males to at most one successful clutch annually. Male RS is limited to a maximum of 4 chicks, whereas females might produce up to 20 (Oring et al 1983;Lank et al 1985).…”
Section: Variation In Male Rsmentioning
confidence: 99%